ASPECTS OF INTERNATIONAL TAX COMPETITION: LITHUANIAN EMPIRICAL EVIDENCE BASED ON SVAR APPROACH - Klyvienė, Violeta (Ekonomika, 2013)
Abstract. This paper aims to investigate the effects of tax policy on macroeconomic variables in the context of tax competition issues. Incentives to invest in a country are determined by a prospective rate of return, which is partially determined by the level of capital taxation. However, high labour mobility, which is a particular characteristic of the Lithuanian economy, raises the hypothesis that the analysis of the negative aspects of tax competition is important not only for capital taxes, but also for labour taxation.Key words: tax competition, SVAR model, capital tax, labour taxes, foreign direct investmentJEL classification: E62, H25, F21.